АНАЛИЗ ВНЕДРЕНИЯ СУДЕБНЫХ УСТАВОВ 1864 г. в БЕССАРАБИИ - Боршевский, Андрей Петрович (SUPREMANCE OF LAW, 2018)
In the present article we have proved that the peace justice of Bessarabia despite the fact that it was based on the principles of the Court Regulations dated of the year 1864 had its own characteristic and distinctive features in comparison with the analogue bodies in the Russia Empire.